A review on developments of in-vitro and in-vivo evaluation of hybrid PCL-based natural polymers nanofibers scaffolds for vascular tissue engineering. (13th September 2022) - Kazemzadeh, Gholamhosein; Jirofti, Nafiseh; Kazemi Mehrjerdi, Hosein; Rajabioun, Masoud; Alamdaran, Seyed Ali; Mohebbi-Kalhori, Davod; Mirbagheri, Mahnaz Sadat; Taheri, Reza
The main objective of the present review article is to investigate the in-vitro and in-vivo biocompatibility behavior of hybrid PCL-based scaffolds with collagen, gelatin, and chitosan to improve endothelialization for VTE applications. It is reported that the high-rate failure of small diameters vascular grafts (SDVGs, <6 mm) due to adhesion of platelets and plasma protein and aggregation, over-proliferation of smooth muscle cells (SMCs), and neointimal hyperplasia at the implantation site is main challenge in vascular tissue engineering (VTE). The fast re-establishment of a functional endothelial cell (EC) layer representing a crucial importance strategy has been proposed to reduce these adverse outcomes. Polycaprolactone (PCL), with optimum mechanical properties, it showed great potential in biomedical applications, but its biocompatibility is still highly concerned in VTE. Modifications of the PCL vascular grafts by developing the hybrid structures using natural polymers with optimum hydrophilicity and biocompatibility properties in order to speed up the re-endothelialization process have been proposed over the last years. Analyzing the mentioned results in the present study can offer a better understanding of the benefits and challenges of applying the natural polymer as a thrombotic response upon implantation in clinical trials. Also, it can suggest the PCL-Collagen as the best framework for the fabrication of rationally designed SDVGs for VTE.